2019
DOI: 10.1016/j.bja.2019.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Pain management decisions in emergency hospitals are predicted by brain activity during empathy and error monitoring

Abstract: Objective: Pain undertreatment, or oligoanalgesia, is frequent in the emergency department (ED), with major medical, ethical, and financial implications. Across different hospitals, healthcare providers have been reported to differ considerably in the ways in which they recognise and manage pain, with some prescribing analgesics far less frequently than others. However, factors that could explain this variability remain poorly understood. Here, we used neuroscience approaches for neural signal modelling to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 36 publications
(43 reference statements)
0
52
0
Order By: Relevance
“…Concerns for such side-effects (e.g. opiophobia) contribute to inadequate pain treatment in medical settings ( Bennett and Carr, 2002 ; Bertrand et al, 2021 ; Corradi-Dell'Acqua et al, 2019 ), as healthcare providers prioritize those cases in which pain is unequivocally established. In this perspective, one study showed that doctors and nurses tended to underestimate pain in larger extent when presented with cues that patients might have lied or exaggerate their ratings ( Kappesser et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns for such side-effects (e.g. opiophobia) contribute to inadequate pain treatment in medical settings ( Bennett and Carr, 2002 ; Bertrand et al, 2021 ; Corradi-Dell'Acqua et al, 2019 ), as healthcare providers prioritize those cases in which pain is unequivocally established. In this perspective, one study showed that doctors and nurses tended to underestimate pain in larger extent when presented with cues that patients might have lied or exaggerate their ratings ( Kappesser et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical settings, acknowledging high levels of pain often leads to the prescription of strong analgesics, which however have contraindications for patients' health (Buckeridge et al, 2010;Butler et al, 2016;Makris et al, 2014). Concerns for such side-effects (e.g., opiophobia) contribute to inadequate pain treatment in medical settings (Bennett and Carr, 2002;Bertrand et al, 2021;Corradi-Dell'Acqua et al, 2019), as healthcare providers prioritize those cases in which pain is unequivocally established. In this perspective, one study showed that doctors and nurses tended to underestimate pain in larger extent when presented with cues that patients might have lied or exaggerate their ratings (Kappesser et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Empathy and risk taking were shown to be some of the factors impacting on how patients with pain were managed in the emergency department. 14 Management of patients with chronic non-malignant pain using long-term potent opioids has been the subject of much discussion, with concerns about increasing addiction and dependence rates, and the contribution that surgery may make to this problem. 15,16 The IASP has produced a position statement around the use of opioids for chronic pain, which reflects these concerns, although ensuring that continued, appropriate use of opioids in acute and cancer pain management is important, especially in lower-and middle-income countries.…”
mentioning
confidence: 99%
“…Our study shows an association between the SUS and the ATMS. Even though this association does not demonstrate a causal link nor is proof of a lower opioid prescription rate, we showed recently that nurses with a higher SUS were less likely to use a nurse-led pain protocol [ 29 ]. SUS may prove to be a new malleable target for educational interventions [ 30 ], and an innovative approach to reduce the burden of unrelieved pain.…”
Section: Discussionmentioning
confidence: 96%